Social Determinants of Health in Menopause: An Integrative Review - Namazi M; Sadeghi R; Behboodi Moghadam Z (Dove Medical Press, 2019)
Masoumeh Namazi,1 Rasoul Sadeghi,2 Zahra Behboodi Moghadam1 1School of Nursing & Midwifery, Tehranct University of Medical Sciences, Tehran, Iran; 2Department of Demography, Faculty of Social Sciences, University of Tehran, Tehran, IranCorrespondence: Zahra Behboodi MoghadamSchool of Nursing & Midwifery, Tehran University of Medical Sciences, Tehran, IranTel +98 9122494201Email Behboodi@tums.ac.irAbstract: Menopause is one of the most important reproductive health issues of women. Because of rising life expectancy, by the year 2030, the global population of menopausal women is expected to include 1.2 billion people. The purpose of the present study is to provide a comprehensive assessment of existing studies on the relationship between social determinants of health and menopause to attract the attention of researchers and health providers to this critical issue. In present integrative review, articles for menopause published from Jan 1990 to Jan 2019 in databases including MEDLINE, ISI Web of Knowledge, Scopus, Google Scholar, IranDoc, IranMedex, MagIran and SID in English and Persian languages were extracted. After the assessment of the inclusion and exclusion criteria, 40 articles were selected and reviewed. Some social determinants of health are related to the health of women in menopause. Cultural factors, lifestyles (nutrition, exercise, tobacco use, etc.), family support, educational level, employment, economic status, marital status, and the number of pregnancies and childbirth are among the social determinants of health that present research assessed them. The need for education, improving emotional and social support, planning for lifestyle enhancement, and improving socio-economic status is felt, which results in promoting women’s health during menopause.Keywords: menopause, lifestyle, cultural factor, socioeconomic status